Complications and survival associated with operative procedures in patients with unresectable pancreatic head adenocarcinoma. Issue 7 (7th January 2014) - Spanheimer, Philip M.; Cyr, Anthony R.; Liao, Junlin; Johlin, Frederick C.; Hoshi, Hisakazu; Howe, James R.; Mezhir, James J.
<x xml:space="preserve">Abstract</x> Background Unresectable tumors of the pancreatic head are encountered in up to 20% of patients taken for resection. The objective of this study was to evaluate the complications and outcome associated with palliative surgical procedures to help guide management decisions in these patients. Methods Patients with pancreatic head adenocarcinoma taken to the operating room with curative intent who did not undergo pancreatectomy were evaluated. Results From 1997 to 2013, 50 patients were explored and found be unresectable due to M1 disease (n = 27, 54.0%) or vascular invasion (n = 23, 46.0%). Among unresectable patients, 34 (68.0%) had a palliative procedure performed including double bypass (n = 13), biliary bypass (n = 7), gastrojejunostomy (n = 5), or cholecystectomy (n = 9). Complications occurred in 22 patients (44.0%), and patients who had a palliative operation had a longer hospital stay and more major complications. Overall survival was reduced in patients treated with a palliative operation. Conclusions Despite advancements in endoscopic palliation, operative bypasses are still commonplace in patients with unresectable pancreatic head cancer. In this study, patients treated with operative procedures had a high rate of complications without a notable improvement in outcome. These findings highlight the importance of identifying unresectable disease prior to surgery and support a selective approach to palliative operations. J. Surg. Oncol 2014; 109:697–701. © 2014 Wiley Periodicals, Inc.